Midwakh: Assessment of Levels of Carcinogenic Polycyclic Aromatic Hydrocarbons and Nicotine in Dokha Tobacco Smoke. Issue 3 (21st January 2021) - Samara, Fatin; Alam, Isra Arshad; ElSayed, Yehya
Abstract: Midwakh, which originated in the Middle East, has started to spread globally with different brands commercialized online and in local stores across Europe and the USA. Dokha is the tobacco used in midwakh. To this day, risk of midwakh smoking is poorly understood. Three different types of dokha were evaluated in this study, classified as cold, medium, and hot using gas chromatography–mass spectrometry (GC–MS). The concentrations of nicotine and polycyclic aromatic hydrocarbons (PAHs) in raw and smoked dokha samples were measured, and the results were compared to data in the literature on different types of tobacco products. PAH concentrations were used to estimate the toxic equivalency quotient, daily exposures, incremental lifetime cancer risk, and hazard quotient. The level of nicotine in raw dokha exceeded by far the levels reported in cigarettes, cigar, waterpipe, and chewing tobacco. Although only a portion of the nicotine is released into the smoke, the amount of nicotine in dokha smoke exceeded those reported for cigarettes. Two PAHs were found in raw dokha at trace amounts and 12 PAHs were detected in dokha smoke in amounts that exceeded those reported for cigarette smoke. The PAHs distribution showed a specific pattern in the smoke and a higher risk factor than that obtained for cigarettes and other tobacco products. Dokha products present a potential higher risk and immediate action should be taken to avoid its global consumption.